Teaching and preaching in the Derveni Papyrus: observations on mantike techne in Archaic and Classical Greece - E. V. Afonasin (Шаги, 2024)
According to a number of ancient authors, including the recently discovered treatise by Galen, “On my own opinions,” Prota goras suggested doubting everything that concerns the gods and their essence. Remarkably, Philostratus (Lives of the Sophists 1.10.2) sees the source of this doubt in Protagoras’ “Persian education” because, in his opinion, the Persian magi, while continuing to call on the gods in their secret rituals, would not admit it publicly, fearing that otherwise people, having realized that their supernatural abilities were linked to divine influences, would stop turning to them. In other words, in this way of reasoning, the magi were anxious not to lose their jobs. Should we accept the historicity of this strange message of Philostratus, or should we consider it a typical reflection of the Hellenistic and Roman historiographic stance to see an “eastern trace” in every doctrine or art? A famous statement from the Derveni papyrus (col. XX), which is fundamental to understanding its authorship, may help us answer this question. We will see the reasons why it is impossible to unequivocally answer the question of whether the author of the papyrus was a practicing telestes. However, it becomes clear that he contrasts himself not with the practitioners of the mysteries (including professional mantis), but with those who participate in them without understanding the meaning of what is going on and “without even asking questions.” On the contrary, he intends to provide answers to possible questions and to reveal the true meaning of the authoritative text by exegetical means. We shall also try to answer the question regarding the purpose for which the author of the papyrus sought to utilize various cosmological associations. Whether we are faced with an ancient philologically oriented “commentator,” or whether, by associating Zeus with air, Moira with pneuma, and Demeter and other female deities with the earth, he seeks to uncover the secret intentionally concealed in the poem and understandable only to the initiated?